2018
DOI: 10.1101/446773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interaction of modified oligonucleotides with nuclear proteins, formation of novel nuclear structures and sequence-independent effects on RNA processing

Abstract: max 150 words) 9Oligonucleotides and nucleic acid analogues that alter gene expression are showing 10 therapeutic promise for selected human diseases. The modification of synthetic nucleic acids 11 to protect against nuclease degradation and to influence drug function is common practice, 12 however, such modifications may also confer unexpected physicochemical and biological 13properties. Here we report backbone-specific effects of modified oligonucleotides on 14 subnuclear organelles, altered distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Immunofluorescent staining of NONO showed that all 2′-Me PS AOs sequestrated NONO, at various subcellular locations (Figure 4A), while the identical sequences synthesised as PMOs had no such effects (Figure 4B). Consistent with the report by Flynn et al (2018) [18], the Gene Tools control sequence seemed to induce the highest amount of NONO-containing nuclear inclusions when applied as a 2′-Me PS AO. All 2′-Me PS sequences tested in this study did induce NONO inclusions in most cells, some inclusions were located within the nucleus while others appear to be peri-nuclear or distributed in the cytoplasm (Figure 4A).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Immunofluorescent staining of NONO showed that all 2′-Me PS AOs sequestrated NONO, at various subcellular locations (Figure 4A), while the identical sequences synthesised as PMOs had no such effects (Figure 4B). Consistent with the report by Flynn et al (2018) [18], the Gene Tools control sequence seemed to induce the highest amount of NONO-containing nuclear inclusions when applied as a 2′-Me PS AO. All 2′-Me PS sequences tested in this study did induce NONO inclusions in most cells, some inclusions were located within the nucleus while others appear to be peri-nuclear or distributed in the cytoplasm (Figure 4A).…”
Section: Resultssupporting
confidence: 90%
“…Phosphorothioate backbone AOs have resulted in severe injection site reactions, thrombocytopenia and renal toxicity in clinical studies [16,17]. An in vitro study by Flynn et al (2018), demonstrated severe, sequence-independent backbone-specific effects of 2′- O -methyl modified bases on a phosphorothioate backbone (2′-Me PS) AOs, including altered distribution of nuclear proteins, the appearance of abnormal but highly structured nuclear inclusions and aggregates and global disturbance of the transcriptome [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the cells did not survive. Possibly due to their toxicity [ 29 ], 2′-OMe AOs targeting COL7A1 exons 10 and 73 tested at concentrations higher than 50 nM (approximately one femtomoles per cell) using Lipofectamine 3000 showed reduced transfection efficiency and a notable increase in cell death. The 150 µM concentration of PMO used in this study was nucleofected into a larger number of cells and hence the calculated number of molecules per cell (approximately 0.1 femtomoles) was roughly tenfold less compared to the highest 2′-OMe AO treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, gapmers modified with LNAs show acute hepatotoxicity in mice (Kasuya et al, 2016). We and others have previously reported that AOs on a fully modified phosphorothioate backbone recruited nuclear proteins involved in RNA processing and induced global disturbance of cellular processes (Shen et al, 2014;Flynn et al, 2018).…”
Section: Discussionmentioning
confidence: 98%